The benefits of intellectual property rights in EU Free Trade Agreements: Full report - Fredrik Erixon; Oscar Guinea; Philipp Lamprecht; Erik Van der Marel (European Centre for International Political Economy (ECIPE), 2022)
This study brings together two major sources of growth in the modern economy: trade and new ideas. Trade is a crucial process to improve economic specialisation and raise the productivity of economies. It is also a channel to diffuse technology and knowledge across countries. International exchange is therefore helping countries to modernise their economies. New ideas are all the innovations, technologies, know-how and business models that gradually power the economy - the intangible assets that define a significant part of modern economic growth. They are the basis for a society's stock of intellectual property, and that stock increases every time there are investments in research and development, production methodologies, brands, novel product design, business know-how and new artistic creations. Most societies allow for protection of intellectual property because intellectual property is necessary for prosperity. Our mission for this multi-year study was to get a much better and granular understanding of what role that intellectual property rights (IPRs) play for trade, productivity and growth, and how trade policies for IPRs have developed over time. Even by our cautious estimates, the results are very clear: copyrights, geographical indications, patents, trademarks and other intellectual property rights support trade and value added in Europe, and stronger IPR provisions in Free Trade Agreements (FTAs) increase the payoff even more.
Keywords: 330; Immaterialgüterrechte; Freihandelsabkommen; Handelsabkommen; EU-Staaten; Welt